THE QURAN AND THE DOWRY-GIVING TRADITION: A RELIGIOUS AND CULTURAL PERSPECTIVE ANALYSIS - Rahmat Munadir (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to reveal the relationship between the values contained in the Qur'an and the traditional practice of dowry (mahr) giving, viewed from both religious and cultural perspectives. Using a qualitative approach based on the textual analysis of Qur'anic verses and in-depth interviews with experts in religious studies and cultural anthropology, this research integrates the frameworks of maqasid al-sharia and cultural anthropology theory to analyze the historical and contemporary transformation of dowry practices. The study also explores the symbolic meaning of dowry, not merely as an obligation but as a form of recognition of women's dignity and rights within the family. Furthermore, it examines the socio-economic factors influencing the amount of dowry and how these factors affect social structures and gender relations within society. In addition, comparisons are made with dowry practices in various other cultures and religions, enabling a deeper understanding of both the unique and shared aspects of universal human values. This comprehensive analysis seeks to provide new insights and a concrete contribution to contemporary discussions on the role of religion in social and cultural life, as well as the challenges of integrating tradition with the needs of modern society. The findings indicate that the practice of dowry giving, as prescribed in the Qur'anic verses, possesses profound normative and strategic values in ensuring justice and social balance within the family structure. Every element of the dowry is not merely symbolic but also embodies meanings that reflect responsibility, respect, and commitment in married life. Over time, the understanding and implementation of this tradition have undergone significant changes, influenced by evolving social, economic, and cultural conditions. This highlights the importance of not only preserving the tradition but also adapting it to meet the demands of contemporary society.